Stone Density Detected by Non Contrast Computed Tomography (Low Dose) Is a Predictor of Successful Outcome of Renal Stone Clearance by Extra Corporeal Shock Wave Lithotripsy - Amin, Mohammad Al; Islam, Md Saiful; Ali, SM Yunus; Choudhury, Md Golam Mowla; Rahman, Mohammed Mizanur (Bangladesh Journal of Urology, 2020)
Objective- To evaluate the usefulness of measuring stone density in Hounsfield Unit by Low-dose Non Contrast Computed Tomography scan in predicting the outcome of extracorporeal shockwave lithotripsy for renal stone clearance. Materials & Methods - A total of 96 patients with renal stone size d” 20 mm attending at the OPD of BSMMU were included in this study. The outcome measures were complete clearance of stone, number of ESWL sessions and number of shock waves required to become stone free. Result- The mean size of the stone was 1.8 ± 0.3 cm. The mean stone density was 663.7 ± 69.8 HU. 25% of the patients underwent 2 sessions of ESWL, 52.1% three sessions and 22.9% more than 3 sessions. Of the patients 83.3 % were successfully cleared of their stone. The mean number of shock waves 6689.2±268.4 required for stone fragmentation of d” 750 HU and 9945±375.7 required > 750 HU stone density respectively. 85.5% of the patients with stone density d” 750 HU needed d” 3 sessions to become stone-free; whereas only 55.5% of the patients with stone density > 750 HU became stone-free in d” 3 sessions. 14.5% patients needed > 3 sessions of ESWL with stone density of e” 750 HU. 78.8% of the patients with stone density d” 750 HU exhibited complete clearance of stone as opposed to 37.5% of those with stone density > 750 HU. The chance of having complete stone clearance is 6-fold (95% CI = 1.9-19.4) higher in patients with low density stone (d” 750 HU) than that in patients with high density stone (d” 750 HU) (p = 0.002). Conclusion-In conclusion a stone density less than 750 HU should be treated with ESWL as first choice of treatment. Bangladesh Journal of Urology, Vol. 19, No. 2, July 2016 p.90-97